Sinkronisasi Perencanaan Pembentukan Peraturan Daerah Dengan Rencana Pembangunan Jangka Menengah Daerah Berdasarkan Peraturan Perundang-undangan - Dahana, Smara; I, Arfa; Hepni, Aswari (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This thesis discusses and describes and analyzes Law Number 12 of 2011 concerning the Formation of Legislation, especially at the planning stage of the formation of regional regulations. In accordance with Article 34 paragraph (1) letter b of Law Number 12 of 2011 concerning the Formation of Legislation, the planning of the formation of regional regulations contained in PROPEMPERDA is based on the regional development plan, but in order to implement this mandate, there is no norm in Law Number 12 of 2011 concerning the Formation of Legislation that regulates how PROPEMPERDA is prepared based on the regional development plan, one of which is the Medium-Term Development Plan (RPJMD), so that PROPEMPERDA and RPJMD are not synchronized, which can hinder regional development. This research is a normative juridical research using a legislative approach and a conceptual approach with the aim of finding the right regulatory norms in synchronizing PROPEMPERDA with RPJMD. The research results yielded ideas for synchronizing the Regional Development Plan (PROPEMPERDA) with the RPJMD, namely: 1. The existence of norms that contain and regulate the preparation of medium-term PROPEMPERDA, involving regional apparatus that organizes regional government affairs for regional planning (hereinafter referred to as BAPPEDA). 2. The existence of norms regulating the improvement of human resource competencies that carry out the preparation of PROPEMPERDA. Keywords: synchronization, formation of regional regulations, regional development planning, PROPEMPERDA, RPJMD.